Emperipolesis and S100 expression may be seen in cutaneous xanthogranulomas: A multi‐institutional observation. (19th June 2018) - Ruby, Kristen N.; Deng, April C.; Zhang, Jingwei; LeBlanc, Robert E.; Linos, Konstantinos D.; Yan, Shaofeng
Abstract : Cutaneous Rosai‐Dorfman disease (RDD) can be difficult to distinguish from other non‐Langerhans cell histiocytoses, particularly xanthogranuloma (XG). Pathologists use S100 immunoreactivity, abundant plasma cells, and the presence of emperipolesis to distinguish RDD from XG. However, S100 expression has been reported in XG and, in practice, we have occasionally observed emperipolesis in cases that were otherwise clinically and pathologically consistent with XG. We present 10 cases of XG with emperipolesis and variable S100 immunoreactivity. Histologically, 7 cases were most in keeping with XG, and a histologic differential of XG versus RDD was raised in the remaining 3 cases. All 10 cases were clinically consistent with XG. Notably, none of these cases showed abundant plasma cells. Nine cases showed variable S100 immunostaining, ranging from focal/weak expression, to focal/strong, diffuse/moderate, and diffuse/strong expression. Histiocytes in all cases were CD68 positive and CD1a negative. We conclude that emperipolesis and S100 expression in a skin biopsy cannot reliably distinguish XG from cutaneous manifestations of RDD. Clinical correlations are essential, as are histologic clues to a diagnosis of classic XG that include an abundance of foamy mononuclear cells, Touton giant cells, and an absence of pale‐stained histiocytes, abundant plasma cells, fibrosis, or vascular proliferation.